THE RELATIONSHIP BETWEEN EDUCATION AND WORK: A CONTEXT OF CONTRADICTIONS AND THE APPROACH TO PROFESSIONAL EDUCATION - Taise Tadielo Cezar; Liliana Soares Ferreira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This text was produced from a bibliographical study, which aims to present brief reflection on the categories work and education, followed by an analysis of how these are embedded in the discourse of current public policy on vocational education, especially in the creation document the Federal Institutes of Education, Science and Technology - Ifs. They were considered for the study theoretical productions of authors who have studied on these two main categories, contextualized in historical and political movements of vocational education in Brazil. From these readings, there was documentary analysis of legislation and peripheral texts dealing Law No. 11,892, dated December 2008, which establishes the Federal Vocational and Technological Education Network and provides new institutional framework to Schools Federal Technical and federal Centers for Vocational and Technological Education, the CEFETs. This analysis was to meet in an attempt to understand how and whether such legislation addresses, within his speech, the categories work and education.